Towards Natural Interaction: Hand Landmark Detection for Robotic Arm Control - ., Aditya; Mallik, Aman Kumar; D, Mithun B; Koul, Shashank (International Journal of Membrane Science and Technology, 2023)
In recent years, the integration of computer vision algorithms and robotics has shown great potential for revolutionizing various domains, including medical sciences. This paper aims to explore the cutting-edge applications of computer vision and robotics in medical research and healthcare. By leveraging the capabilities of computer vision algorithms and robotic systems, we can enhance medical diagnosis, surgical interventions, and patient care. This research paper provides an in-depth analysis of the key components, challenges, and potential future directions of this interdisciplinary field. In this paper, we propose an innovative approach to addressing the scarcity of professional medical assistance in isolated communities by establishing efficient communication between the human operator and a robotic limb that has enabled the precise replication of human movements in real-time by implementing computer vision, regardless of geographical distance, thereby revolutionizing the remote operation of such robotic devices. This advanced artificial body part aims to perform not only basic health check-ups but also has the potential for more complex medical procedures. Our approach overcomes limitations of existing prosthetic models, such as pre-determined task-specific functionalities and high latency in real-time operation as well as the necessity for the operator and the robotic unit to be nearby. Furthermore, the proposed model reduces the need for frequent calibration and constant monitoring, enhancing its practical applicability. It can also collect valuable medical data, providing patients with a reliable means of tracking their health conditions and medical professionals with vast amounts of structured medical data previously inaccessible. We aim to inspire further research and development in the field of computer vision algorithms and robotics for advancements in medical sciences. Through this interdisciplinary work, we anticipate improved healthcare access and outcomes for individuals residing in isolated communities, ultimately contributing to the overall enhancement of medical services on a global scale.